The prospects of sport event tourism development in Kazakhstan (Journal of Geography and Environmental Management, 2018)
The essence and the definition of sport event tourism are disclosed in this paper. Author’s classification of sports events is offered. Modern problems of large sports event organization were investigated. Current trends in sport event tourism development were identified. The development of sport event tourism has promising prospects in Kazakhstan. The presence of resource potential as the combination of ancient traditions and large-scale events of the modern period, multicultural environment and locals’ tolerance, economic stability and increased business cooperation along with advances in science, education, sport, environmental protection and other spheres of human activity stimulates the interest of a world community and the growth of foreign visitor number. The XXVIII Winter Universiade held in Almaty became the first worldwide multi-sport event in the history of independent Kazakhstan. FISU Expert council (International University Sports Federation) recognized Winter Universiade in Almty as the best in the history of worldwide sports competitions for student-athletes.